The Role of Antioxidants as Adjuvants of Fibromyalgia Management - Sabrina Chusnul Chotimah (Indonesian Rheumatology Associantion, 2023)
Fibromyalgia is a condition with complex polysymptomatology characterizedby chronic widespread pain, fatigue, sleep disturbances, and functionalsymptoms. Oxidative stress plays a role in the etiology of pain which is themain symptom of fibromyalgia. The symptoms of fibromyalgia are related tothe balance of oxidant and antioxidant. Antioxidants from certain nutrientscan act to counter the high level of free radicals, in order to maintain theoxidative stress/antioxidant balance. Antioxidant such as coenzyme Q10,vitamin C and E, magnesium, and acetyl-L-carnitine have the potentialbenefit as adjuvants in treating fibromyalgia by reducing pain.